AUTONOMOUS VS. CONTROLLING EDUCATIONAL ENVIRONMENTS - Matric, Maja (Journal of process management and new technologies, 2019)
Active and motivated students are much desired in the educational context. Learning how to lead the students to find intrinsic motivation for schoolwork, help them self-regulate their learning and feel autonomous in the learning process is an important task of every educator. In the article, we present autonomous and controlling educational environments in terms of motivation and regulation. We report of research which has examined the benefits of autonomy supportive learning and provide concrete guidelines teachers can adhere to in order to move away from controlling instruction, thus boosting the students perceived autonomy, self-regulation and motivation for schoolwork.